Research of technological factors impact on obtaining process of dairy-protein co-precipitates with viburnum - Gnitsevych, Victoriya; Deinychenko, Liudmyla (My University, 2016)
В статті досліджено вплив температури та рН на осадження білків сколотин, обрано режими осадження. В статье исследовано влияние температуры и рН на осаждение белков пахты, избраны режимы осаждения. The influence of temperature and pH on precipitation of buttermilk proteins was investigated, precipitation modes were selected.
Keywords: сколотини; калина; молочно-білкові копреципітати; пахта; молочно-белковые копреципитаты; buttermilk; viburnum; milk-protein co-precipitates; кафедра технології ресторанної і аюрведичної продукції